LEGAL PROTECTION OF HEALTH PERSONNEL PERFORMING DUTIES DURING THE COVID-19 PANDEMIC - Adelia Nur Asshilah; Zainudin Hasan (Jurnal Ilmiah Advokasi, 2023)
During this Covid-19 pandemic, many problems have been found that have been faced by health workers in carrying out health service tasks that have the potential to not guarantee legal certainty. The purpose of this study was to determine the factors causing criminal acts by health workers during the Covid-19 pandemic. The research method used is a normative juridical approach by collecting data from literature studies. Based on the research that has been done, it is found that health workers may experience crime from the community, which occurs due to several factors. Pancasila has an ideology and philosophical basis so the principle of legal protection for the Indonesian people is the principle of recognition and protection of human dignity based on Pancasila and the principle of the rule of law based on Pancasila. In other words, the concept of legal protection is an illustration of the function of law, namely the concept that the law provides justice, order, certainty, benefit, and peace. Legal protection for health workers during the COVID-19 pandemic consists of preventive protection efforts and repressive protection efforts. Preventive Protection which is defined as prevention, in other words, is the freedom to act because of the content contained in the legislation to prevent a violation. Repressive Protection serves to solve problems. This protection is in the form of sanctions for violations committed.Keywords: Health Workers, Crime Factors